Parallel Sponge-Based Authenticated Encryption With Side-Channel Protection and Adversary-Invisible Nonces - Jimale M.A.; Z'Aba M.R.; Kiah M.L.B.M.; Idris M.Y.I.; Jamil N.; Mohamad M.S.; Rohmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bridges; Side channel attack; Authenticated encryption; CAESAR competition; Cipher; Code; Confidentiality; Cryptographic sponge function; CryptoGraphics; Integrity; Message authentication codes; NIST; NIST-LW competition; Security; Sponge functions; Authentication